Bringing the Community Along: A Case Study of a School District's Information Technology Rural Development Initiative - Kai A. Schafft; Theodore R. Alter; Jeffrey C. Bridger (Journal of Research in Rural Education, 2006)
We draw on interactional community theory to analyze the relationship between information technology and local development through a case study of a geographically isolated and economically disadvantaged rural school district. This district has used state-of-the-art information technology infrastructure in a broad-based community and economic development effort. We assess community outcomes across three dimensions: educational improvement, community identity, and economic development. We find that this effort has had significant positive effects on the first two dimensions, but economic impacts have been far less pronounced, raising questions about telecommunications technology as the new catalyst for rural economic revitalization.